2017
DOI: 10.1177/1179555717722962
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Cryptococcosis Presenting With Lung Mass: Report of 7 Cases and Review of Literature

Abstract: Pulmonary cryptococcosis is commonly found in immunocompromised patients. This microorganism rarely infects immunocompetent individuals, and when it does, it causes mild symptoms. The radiological findings of this disease may involve an intrapulmonary mass that mimics lung tumor. The objective of this study was to review the clinicopathological information, radiological findings, and treatment of patients who presented with intrapulmonary mass due to cryptococcosis. This study collected data from 7 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…The common CT manifestations of pulmonary cryptococcosis were solitary or multiple pulmonary nodules or masses [ 17 ], making it difficult to distinguish cryptococcosis from malignant tumor and bacterial pneumonia. It has been reported that among cases of pulmonary cryptococcosis coexisting with lung cancer, adenocarcinoma is the main histological type, probably because cryptococcosis is apt to occur in the periphery of the lung, where adenocarcinoma is commonly found [ 18 ]. Cavitation and halo sign are more frequently observed in immunocompromised patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The common CT manifestations of pulmonary cryptococcosis were solitary or multiple pulmonary nodules or masses [ 17 ], making it difficult to distinguish cryptococcosis from malignant tumor and bacterial pneumonia. It has been reported that among cases of pulmonary cryptococcosis coexisting with lung cancer, adenocarcinoma is the main histological type, probably because cryptococcosis is apt to occur in the periphery of the lung, where adenocarcinoma is commonly found [ 18 ]. Cavitation and halo sign are more frequently observed in immunocompromised patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…6. Radiographic findingsin case of immunocompetent patients-Typical findings: intrapulmonary mass up to 3 cm in size, lung consolidation or a reticulonodular pattern [22] .…”
Section: Diagnosis: Cryptoccocosis Is Identified By Following Tests -1 Direct Microscopy -Csf Mixed Withmentioning
confidence: 99%
“…The immune tolerance induced by LPS could, in part, explain T-cell dysfunction in sepsis syndrome -which is reversible by exogenous IL-7 administration in patients (Francois et al, 2018). A study in mice showed that trained immunity in DC driven by protective vaccination against Cryptococcus neoformans, an opportunistic fungal pathogen of the lungs (Kanjanapradit et al, 2017), allowed the trained DCs to generate stronger pro-inflammatory responses against bacterial pathogens in vitro, suggesting an effect of trained immunity (Hole et al, 2019).…”
Section: Macrophages and Dendritic Cellsmentioning
confidence: 99%